Functional and Physicochemical Properties of Milled and Microfluidized Bulgur and Chickpea Brans - Burcu Baumgartner; İrem Saka; Berrin Özkaya; Hazım Özkaya (Journal of Agricultural Sciences)
Dietary fiber plays a crucial role in human diet due to their healthpromoting effects. Cereal brans are widely used for fiber enrichment of bakery products; however, their high phytic acid content, mostly localized in the aleurone layer, lowers the nutritional value of the endproduct. Therefore, the functional and physicochemical properties of two aleurone-free brans, bulgur and chickpea brans, were investigated as alternative fiber sources. Furthermore, effect of particle size reduction by means of milling and the microfluidization process on these properties were determined. The microfluidization reduced the particle sizes of bulgur and chickpea brans to 13.12 and 14.25 μm, respectively. The results indicated that the microfluidization significantly increased the soluble dietary fiber content of brans. Thus, the insoluble/ soluble dietary fiber ratios of bulgur and chickpea brans decreased to 8.42 and 6.13 from 19.20 and 15.33, respectively. The phytic acid contentsranged from 230.8 to 247.9 mg/100g for bulgur bran, and 112.1 to 113.1 mg/100g for chickpea bran. After the microfluidization, these contents decreased to 107.1 and 47.9 mg/100g for bulgur and chickpea brans, respectively. The milled samples did not show any differences in terms of phenolic contents and antioxidant activity, but the microfluidization increased the phenolic content of bulgur and chickpea brans as 73.80% and 59.62%, respectively. In addition, the antioxidant activity values increased 73.08% for bulgur bran, and 76.70% for chickpea bran with this process. Chickpea bran had higher swelling and water holding capacity than that of bulgur bran, but the oil holding capacities of both types of brans were close to each other. Conventional milling had nosignificant effect on these properties, whereas the microfluidization improved them. Therefore, it can be said that the applied microfluidization process enhanced physicochemical properties along with their functional properties, and it is possible to degrade phytic acid with microfluidization process.